SyncHolo: Holograms in the World of Art - Rocca, Paola; Rai, Caterina; di Giacomo, Camilla (Archeomatica, 2023)
The use of holograms in exhibition design and the new frontier of inclusive communication to the public: how holograms enrich the cultural experience and how digital technology synthesizes the analog into experiences that amplify the perception of art and its meaning. When introduced to the topic of holograms for the first time, one's mind may wander to a diverse archive of pop culture and science fiction, transporting us to the distant worlds of Star Wars or Star Trek, or to the advertisements from Back to the Future. At first glance, holograms appear as nothing more than a fantasy, a glimpse into a technology seemingly too advanced for our time. However, enthusiasts know that the era of holograms has begun, and we are already engaged in an ongoing technological pursuit. Experts in the field are aware that technology's evolution has impressively expanded the horizons of hologram applications.